Metanephrine negative pheochromocytoma: a rare case report of dopamine-secreting tumor in an adolescent neurofibromatosis type 1 patient - Mi-Seon Lee; Rosie Lee; Sook-Hyun Park; Soon Hak Kwon; Jin-Young Park; Sang-Woo Lee; So-Mi Lee; Jung-Eun Moon (Korean Society of Pediatric Endocrinology, 2022)
Pheochromocytoma (PCC) occurs in 4% of pediatric neurofibromatosis type 1 (NF1) patients and is characterized by epinephrine and norepinephrine secretion. Herein, we report the first case of dopamine-secreting PCC in a 13-year-old patient with NF1. A left adrenal mass was incidentally found on abdominal computed tomography (CT) during hypertension workup. Fractionated 24-hour urine metanephrine excretion was normal, but urine dopamine level was elevated. Focal 123I-metaiodobenzylguanidine uptake was observed on single-photon emission tomography/CT (SPECT/CT). Surgery was delayed due to small tumor size, vague symptoms, and increased dopamine level. After 6 months, focal significant uptake of the lesion on 6‐[18F]fluoro‐L‐3,4‐dihydroxyphenylalanine (18F-FDOPA) PET/CT increased and tumor size increased on abdominal CT. Laparoscopic resection was performed, and the mass was histologically confirmed as PCC. Currently, the vital signs of the patient are stable, urine dopamine level is normal, and there is no abnormal uptake of 18F-FDOPA PET/CT. This study reports a rare case of dopamine-secreting PCC. A multidisciplinary approach and focused examination are needed in metanephrine-negative, high-risk PCC patients.